EFEKTIVITAS PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN PRODUKSI PADI DI KELURAHAN KERAMASAN DAN KARYA JAYA KOTA PALEMBANG - Raymondo Felix Sipayung; Selly Oktarina; Usman Apriadi (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to assess the extent to which the role of agricultural extension workers contributes to increasing rice production in Keramasan and Karya Jaya villages, Palembang City. The primary focus of this study is on the significance of the presence of extension workers as a liaison between government policies and farming actors, particularly in enhancing the productivity of strategic food commodities such as rice. The adopted methodology is descriptive quantitative, employing a questionnaire administered to 30 farmers as a data collection instrument. These farmers were selected through a purposive sampling method. The effectiveness of the role of extension workers was measured through five main indicators, namely communicators, educators, motivators, facilitators, and dynamists, with the help of a Likert scale. The results obtained from this study indicate that extension workers have a very significant influence on increasing productivity, especially through their facilitator and educator functions. This finding underscores the pivotal role of optimized extension functions in fostering sustainable agricultural development in urban contexts.